Providing for the People : Policy Note on Utility Service Reform in Mauritania's Mining Corridor - World Bank (Washington, DC, 2014)
This policy note summarizes the results of a Poverty and Social Impact Analysis (PSIA) and a consultative decision making process carried out over a two-year period (2005-2007). Chapter two presents the country and reform context by providing background information on the role of mining in Mauritania's economy and explaining the current situation in the Nouadhibou-Zouerat economic corridor with regard to water and electricity services. This section indicates the need for reform by reviewing the reform context from a legal, economic, institutional, technical, and consumer perspective. Chapter three introduces previous reform proposals and discusses the economic viability of the most plausible reform option. Chapter four outlines the potential social and poverty impacts of utility service reform by presenting survey results on consumers' ability and willingness to pay, showing which social groups are at risk of being negatively affected by reform and exploring policy responses to the identified risks. It also weighs the risks associated with reform against its benefits and provides policy recommendations. Issues associated with the political economy of reform implementation are discussed in chapter five, which concludes by making specific recommendations for the implementation of the necessary reform measures (chapter six).